2017
DOI: 10.1038/nn.4494
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity modifies the chromatin accessibility landscape in the adult brain

Abstract: Neuronal activity-induced gene expression modulates the function and plasticity of the nervous system. It is unknown whether and to what extent neuronal activity may trigger changes in chromatin accessibility, a major mode of epigenetic regulation of gene expression. Here we compared chromatin accessibility landscapes of adult mouse dentate granule neurons in vivo before and after synchronous neuronal activation using ATAC-seq. We found widespread, genome-wide changes one hour after activation, with enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
235
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(268 citation statements)
references
References 58 publications
31
235
2
Order By: Relevance
“…We found that learning increases chromatin accessibility genome-wide, supporting previous findings that neuronal activation increases chromatin accessibility (35). Our results, however, provide a genome-wide map of chromatin remodeling in response to behavior.…”
Section: Discussionsupporting
confidence: 90%
“…We found that learning increases chromatin accessibility genome-wide, supporting previous findings that neuronal activation increases chromatin accessibility (35). Our results, however, provide a genome-wide map of chromatin remodeling in response to behavior.…”
Section: Discussionsupporting
confidence: 90%
“…For gene expression analysis, the total RNA fraction was immediately isolated from cultured mouse neural progenitor samples with RNeasy Mini Kit (Qiagen), treated with DNaseI and reverse-transcribed into the first-strand cDNA with SuperScript III (Thermo Fisher Scientific) (Su et al, 2017). cDNAs were used for SYBR-green based quantitative real-time PCR to measure the expression level of target genes with the comparative CT method (ABI) (Su et al, 2017).…”
Section: Star Methodsmentioning
confidence: 99%
“…cDNAs were used for SYBR-green based quantitative real-time PCR to measure the expression level of target genes with the comparative CT method (ABI) (Su et al, 2017). The primers used for quantitative PCR are listed in Table S1.…”
Section: Star Methodsmentioning
confidence: 99%
“…Detailed analysis of the chromatin accessibility in neurons with differential regenerative capacities will therefore be instrumental in engineering and developing new strategies to direct axon regeneration. Indeed, recent technical developments now enable researchers to study transcription and chromatin accessibility in a cell-type-specific manner 157 and have been applied to show that neuronal activity modifies the chromatin accessibility landscape in the adult brain 158 .…”
Section: Transcriptional Changesmentioning
confidence: 99%